Sloanea pacuritana Pal.-Duque, sp. nov. (Elaeocarpaceae) del Chocó (Colombia) - Leonardo Palacios-Duque (Anales del Jardín Botánico de Madrid)
A new species of the central Chocó (Colombia) rainforest is described: Sloanea pacuritana. The new species is included in subgenus Sloanea section Sloanea, where it is characterized by large leaves (to 24.4 cm wide) with acute base and apex, narrowly triangular stipules more than 9 mm long, and smooth and tomentose peduncles.